The mechanics of the baby boom: Unveiling the role of the epidemiologic transition. (2nd September 2018) - Gauvreau, Danielle; Sabourin, Patrick; Vézina, Samuel; Laplante, Benoît
Abstract : Recent research on the baby boom and its causes has shown that common explanations, such as the recuperation of births following the Great Depression or Second World War, are not sufficient to account for the phenomenon. However, that research has stressed the role of increasing nuptiality. In this paper, we argue that the increase in survivorship of children and young people that resulted from the epidemiologic transition accounted for a large portion of the increased number of births during the baby boom. We use a microsimulation model to assess the respective roles of mortality, nuptiality, fertility, and immigration on the size and dynamics of the boom in Quebec, Canada. Results show that decreasing mortality contributed significantly to the baby boom, along with immigration and nuptiality changes, while fertility rates attenuated the phenomenon. These results substantiate the hypothesis that the epidemiologic transition was an important cause of the baby boom.